2012
DOI: 10.1128/jvi.06405-11
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus V Proteins Interact with the RNA Helicase LGP2 To Inhibit RIG-I-Dependent Interferon Induction

Abstract: b RIG-I and mda-5 are activated by viral RNA and stimulate type I interferon production. Laboratory of genetics and physiology 2 (LGP2) shares homology with RIG-I and mda-5 but lacks the CARD domains required for signaling. The V proteins of paramyxoviruses limit interferon induction by binding mda-5 and preventing its activation; however, they do not bind RIG-I and have not been considered inhibitors of RIG-I signaling. Here we uncover a novel mechanism of RIG-I inhibition in which the V protein of parainflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 55 publications
4
120
0
Order By: Relevance
“…56 This evasion strategy, while apparently specific for MDA5 and LGP2, may also indirectly act against RIG-I through LGP2 via an undefined mechanism. 56,57 Very little is known about how similar or different LGP2 is from RIG-I or MDA5 in recognizing various RNA ligands. However, recently, Bruns et al demonstrated that robust basal ATPase activity allows LGP2 to diversify its RNA recognition capacity.…”
Section: 5152mentioning
confidence: 99%
“…56 This evasion strategy, while apparently specific for MDA5 and LGP2, may also indirectly act against RIG-I through LGP2 via an undefined mechanism. 56,57 Very little is known about how similar or different LGP2 is from RIG-I or MDA5 in recognizing various RNA ligands. However, recently, Bruns et al demonstrated that robust basal ATPase activity allows LGP2 to diversify its RNA recognition capacity.…”
Section: 5152mentioning
confidence: 99%
“…Rinderpest virus (RPV) may differ, as it appears to use the C protein rather than V to inhibit MDA5 signalling, although the binding of RPV V to MDA5 has not been examined [72] . and Salem virus (SalV) were shown to bind a specific region within/proximal to residues 701-816 of the MDA5 helicase domain, independently of the MDA5 ligand dsRNA [70,71,73] , thereby blocking dsRNA-MDA5 interaction [70] . Although a recent study of PIV5 V identified a change in the dsRNA-binding properties of MDA5 when V was co-expressed, rather than a complete inhibition, suggesting that V may still allow non-cooperative dsRNA binding [74] .…”
Section: Targeting Of Mda5mentioning
confidence: 99%
“…However, recent data has indicated that V proteins can inhibit RIG-Ⅰ by interaction with another cellular helicase, the laboratory of genetics and physiology 2 (LGP2) [73] , via a region of LGP2 homologous to the V protein binding region in MDA5 [71,73] . The interaction appears to be dependent on the unique C-terminal domain of V protein, as PIV5 P protein did not bind to LGP2, but the C-terminal domains of MeV and MuV V proteins were necessary and sufficient for the interaction [71,73] .…”
Section: Targeting Of Rig-ⅰ Via Laboratory Of Genetics and Physiologymentioning
confidence: 99%
“…LGP2 (Cyt) (Childs et al, 2012); STAT1 and STAT2 (Cyt or Nuc ¶) (Ulane & Horvath, 2002); DDB1 (Cyt or Nuc ¶) (Ulane & Horvath, 2002); Cul4A (Cyt) (Ulane & Horvath, 2002); IKK" and TBK1 (Cyt) (Lu et al, 2008) …”
Section: Proteinmentioning
confidence: 99%
“…LGP2 (Cyt) (Childs et al, 2012); STAT1, STAT2 and STAT3 (Cyt or Nuc ¶) (Palosaari et al, 2003); JAK1 (PM) (Caignard et al, 2007); IRF-9 Cyt & Nuc (Precious et al, 1995) Cyt & Nuc (Paterson et al, 1995) N (Randall & Bermingham, 1996) MDA5 (Cyt) (Andrejeva et al, 2004);…”
Section: Mevmentioning
confidence: 99%